2020
DOI: 10.1177/1368430220946816
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes in the face of reality: Intergroup contact inconsistent with group stereotypes changes attitudes more than stereotype-consistent contact

Abstract: In a longitudinal two-wave study we examined the effects of positive and negative intergroup contact on outgroup attitudes in participants who perceived positive, negative, or ambivalent group stereotypes. We focused on stereotype-consistent contact, occurring when the valence of participants’ contact matches the valence of the perceived group stereotype (e.g., negative–negative), and on stereotype-inconsistent contact, occurring when the valence of contact contradicts the valence of the group stereotype (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 58 publications
1
26
0
1
Order By: Relevance
“…Although they found opposing results to Zingora et al. (2020), Paolini and McIntyre (2018) in a meta‐analysis including 59 tests of individual to group generalizations, also examined the effects of prior expectations towards an outgroup. They found that positive information about outgroup members had a greater impact on evaluations of positively stereotyped outgroups, whereas negative contact had a greater impact on the evaluations of negatively stereotyped outgroups.…”
Section: The Emerging Field Of Research On Positive and Negative Contactmentioning
confidence: 92%
See 2 more Smart Citations
“…Although they found opposing results to Zingora et al. (2020), Paolini and McIntyre (2018) in a meta‐analysis including 59 tests of individual to group generalizations, also examined the effects of prior expectations towards an outgroup. They found that positive information about outgroup members had a greater impact on evaluations of positively stereotyped outgroups, whereas negative contact had a greater impact on the evaluations of negatively stereotyped outgroups.…”
Section: The Emerging Field Of Research On Positive and Negative Contactmentioning
confidence: 92%
“…First research suggests that these divergent findings might partially be due to different precontact expectations towards the respective outgroups (e.g., Zingora et al, 2020), or to different outcome measures used in different studies. Although they found opposing results to Zingora et al (2020), Paolini and McIntyre (2018) in a meta-analysis including 59 tests of individual to group generalizations, also examined the effects of prior expectations towards an outgroup. They found that positive information about outgroup members had a greater impact on evaluations of positively stereotyped outgroups, whereas negative contact had a greater impact on the evaluations of negatively stereotyped outgroups.…”
Section: The Emerging Field Of Research On Positive and Negative Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple other mechanisms explaining specifically primary (but not secondary) transfer effects of positive contact have been identified. These comprise affective variables such as different intergroup emotions (e.g., anger: Barlow et al, 2019;disgust and admiration: Cernat, 2011;fear: Kauff et al, 2017;Seger et al, 2017) and numerous cognitive processes (e.g., knowledge about the outgroup: Brown & Hewstone, 2005); social norms (perceptions of how ingroup members think and act: Christ et al, 2014;Paterson et al, 2019;Turner et al, 2008;Wang et al, 2019); inclusion of the other in the self (perceived closeness between the self and outgroup: Page-Gould et al, 2010;Turner et al, 2008); self-disclosure (disclosure of personal information about self to other: Frølund Thomsen, 2012;Turner, et al, 2007); dehumanization or infrahumanization (denying elements of humanness to outgroups: Prati & Loughnan, 2018;Stathi et al, 2017); perceived importance of and satisfaction with contact (Frias-Navarro et al 2020;van Dick et al, 2004); perceived outgroup heterogeneity (perception of similarity between outgroup members: Čehajić et al, 2008); stereotypes of outgroup warmth and competence (Kotzur et al, 2019;Zingora et al, 2020); and metastereotypes (beliefs about the stereotypes that outgroup members hold about their group: Mazziotta et al, 2011). It is plausible to expect many of these processes (e.g., emotions, social norms, outgroup evaluations) to generalize from primary to secondary outgroups and thus underlie not only the primary but also secondary transfer effects.…”
Section: Mediators Of Specifically Primary Transfer Effectsmentioning
confidence: 99%
“…These individuals usually exhibit more negative intergroup attitudes (e.g., Pettigrew et al., 2007; Verkuyten & Brug, 2004). Likewise, primary transfer effects of positive contact are stronger for those who hold more unfavorable outgroup attitudes (e.g., Munniksma et al., 2013) or negative outgroup stereotypes (e.g., Zingora et al., 2020, but see Paolini & McIntyre, 2019). Future research could explore the role of such individual differences in secondary transfer effects, investigating how prejudice‐related variables can favor/hamper the generalization of positive and negative contact effects to other groups, thus shedding light on the reasons why some individuals demonstrate dislike towards multiple outgroups.…”
Section: Introductionmentioning
confidence: 99%